Graphene‐Based Textiles for Thermal Management and Flame Retardancy (Adv. Funct. Mater. 42/2022). (18th October 2022) - Ge, Qi; Chu, Jingwen; Cao, Weiqi; Yi, Fenglian; Ran, Zhou; Jin, Zhan; Mao, Boyang; Li, Zheling; Novoselov, Kostya S.
Abstract : Graphene‐Based Textiles Personal thermal management and fire retardancy are the two important aspects of next generation smart textiles, and graphene and its derivatives have the capability to enable both of them. In article number 2205934, Boyang Mao, Zheling Li, Kostya S. Novoselov, and co‐workers provide an overview of the current progress in this field, and some critical thoughts and perspectives for future studies.